Lesotho : Third Review Under the Poverty Reduction and Growth Facility Arrangement and Request for Waivers of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2002)
This paper assesses Lesotho's Third Review Under the Poverty Reduction and Growth Facility (PRGF) Arrangement and Request for Waivers of Performance Criteria. The government has declared a state of famine that is affecting an estimated 900,000 people. One quantitative performance criterion for end-March 2002-the ceiling on the government's domestic financing requirement-was not observed, almost entirely because of delays in external payments. The authorities have requested, and IMF staff supports, a waiver on this performance criterion.